Mechanisms and Active Compounds Polysaccharides and Bibenzyls of Medicinal Dendrobiums for Diabetes Management - Li, Mingjian; Trapika, I. Gusti Surya Chandra; Tang, Suet Yee Sara; Cho, Jun-Lae; Qi, Yanfei; Li, Chun Guang; Li, Yujuan; Yao, Meicun; Yang, Depo; Liu, Bowen; Li, Rong; Yang, Ping; et al. (Frontiers in Nutrition, 2022)
Abstract Background: Medicinal dendrobiums are used popularly in traditional Chinese medicine for the treatment of diabetes, while their active compounds and mechanism remain unclear. This review aimed to evaluate the mechanism and active compounds of medicinal dendrobiums in diabetes management through a systematic approach. Methods: A systematic approach was conducted to search for the mechanism and active phytochemicals in Dendrobium responsible for anti-diabetic actions using databases PubMed, Embase, and SciFinder. Results: Current literature indicates polysaccharides, bibenzyls, phenanthrene, and alkaloids are commonly isolated in Dendrobium genusin which polysaccharides and bibenzyls are most aboundant. Many animal studies have shown that polysaccharides from the species of Dendrobium provide with antidiabetic effects by lowering glucose level and reversing chronic inflammation of T2DM taken orally at 200 mg/kg. Dendrobium polysaccharides protect pancreatic β-cell dysfunction and insulin resistance in liver. Dendrobium polysaccharides up-regulate the abundance of short-chain fatty acid to stimulate GLP-1 secretion through gut microbiota. Bibenzyls also have great potency to inhibit the progression of the chronic inflammation in cellular studies. Conclusion: Polysaccharides and bibenzyls are the major active compounds in medicinal dendrobiums for diabetic management through the mechanisms of lowering glucose level and reversing chronic inflammation of T2DM by modulating pancreatic β-cell dysfunction and insulin resistance in liver as a result from gut microbita regulation.